2007
DOI: 10.1176/ps.2007.58.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in Postdischarge Suicide After Deinstitutionalization and Decentralization: A Nationwide Register Study in Finland

Abstract: The restructuring and downsizing of mental health services was not associated with any increase in suicides immediately (one week) or one year postdischarge. Instead, the risk of these suicides decreased significantly between the two time periods among several diagnostic categories. Although the role of psychiatric hospitalization in general may have changed over time, patients who are hospitalized now may be less suicidal after discharge. Our results indicate, in terms of postdischarge suicides, that the down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Seventhly, the study covered the years 1987–2003. Whether changes over time increasing the recognition and diagnosis of bipolar disorder, shortening the duration of hospitalizations , or increasing the availability of new pharmacotherapy options for the illness influence the patterns of suicide risk remains unknown. Finally, the generalizability of findings from Finland to other countries is uncertain, despite considerable similarity of epidemiological and register‐based findings with regard to mental disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventhly, the study covered the years 1987–2003. Whether changes over time increasing the recognition and diagnosis of bipolar disorder, shortening the duration of hospitalizations , or increasing the availability of new pharmacotherapy options for the illness influence the patterns of suicide risk remains unknown. Finally, the generalizability of findings from Finland to other countries is uncertain, despite considerable similarity of epidemiological and register‐based findings with regard to mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, it likely varies markedly according to patients' clinical state and the presence of other risk factors (5)(6)(7). Suicide risk in all psychiatric inpatients is known to be high immediately postdischarge, making this period an important target for preventive efforts (8,9). This risk is also very high in patients with affective disorders overall (8)(9)(10), but the temporal patterns of post-discharge suicide risk and the factors modifying risk specifically among bipolar patients are poorly known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of in-patient suicide were still higher than the general population rate at the end of our study period : approximately 600 per 100 000 when expressed in terms of in-patient years (rather than in-patient days as in Table 1), or around 60 times the general population rate. By contrast, studies in Finland have shown reduced post-discharge suicide mortality among patients with severe mental illness over time, despite a smaller number of psychiatric beds (Pirkola et al 2007 ;Rantanen et al 2009). Our figures on the increasing rate of post-discharge suicide should be interpreted with caution.…”
Section: Interpretation Of Findingsmentioning
confidence: 97%
“…Our findings suggest that strategies to further reduce in-patient suicide might focus on the processes for granting leave or preventing unauthorized absences from the ward, as well as the physical ward environment (Appleby et al 2006). It has been suggested that this reduction may, in part, be explained by an increase in psychiatric treatment within primary care facilities in Finland, in addition to improved post-discharge community care (Pirkola et al 2007 ;Rantanen et al 2009). The numbers of such deaths did in fact fall, but because of a large decrease in the number of discharges on the HES database (approximately 34 %), the rates seemed to have increased.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%